Reviewing the links and feedbacks between climate change and air pollution in Europe - Im, Ulas; Geels, Camilla; Hanninen, Risto; Kukkonen, Jaakko; Rao, Shilpa; Ruuhela, Reija; Sofiev, Mikhail; Schaller, Nathalie; Hodnebrog, Øivind; Sillmann, Jana; Schwingshackl, Clemens; Christensen, Jesper H.; et al. (Frontiers in Environmental Science, 2022)
Feedbacks between air pollutants and meteorology play a crucial role in the direction of the response of future climate and air pollution. These feedbacks are important to understand and quantify the potential impact of adaptation and mitigation policies setup for protecting the population against air pollution and heat stress. We review the interactions between climate and air pollution, with special focus on the projections of air pollution under different future climate scenarios and time horizons, based on a literature review of research articles and reports from the last decade. The assessment focuses on (i) the specific impacts of climate change on air pollution and natural particle and precursor emissions in Europe in the near future (2030), by mid-century (2050) and by end of the century (2100), (ii) impacts on air pollution due to changes in emissions vs changes in climate, (iii) feedbacks from air pollution on climate, (iv) impacts of climate change on wildland fires and air pollutant levels, and (v) the role of adaptation and mitigation policies on climate change and air pollution. Available literature to a large extent suggests that ozone concentrations will likely increase in the second half of the century by up to more than 9 ppb, while in the first half of the century, changes are much smaller and are up to +- 1.5 ppb. Increases are mainly attributed to increased temperatures and emissions of biogenic volatile organic compounds. On the other hand, the predicted changes in particle concentrations and chemical composition are uncertain and much smaller . Similar to ozone, larger changes in the particle concentrations are projected in the second half of the century. The main conclusion from this review is that the estimated changes in pollutant levels in the future vary significantly depending on the applied model systems, as well as the different emission or meteorological scenarios used in the different studies. Nevertheless, studies generally agree on the overall trend of the changes in pollutant levels due to climate change, in particular in the second half of the century.